Creative destruction and asset prices - Joachim G. Grammig; Stephan Jank (University of Cologne, Centre for Financial Research (CFR), 2010)
This paper introduces Schumpeter's idea of creative destruction into asset pricing. The key point of our model is that small and value firms are more likely destroyed during technological revolutions, resulting into higher expected returns for these stocks. A two-factor model including market return and patent activity growth - the proxy for creative destruction risk - accounts for a large portion of the cross-sectional variation of size and book-to-market sorted portfolios and prices HML and SMB. The expected return difference between assets with the highest and lowest exposure to creative destruction risk amounts to 8.6 percent annually.
Keywords: G12; 330; creative destruction; asset pricing; size and value premium; patents; Kapitalertrag; Klein- und Mittelunternehmen; Capital Asset Pricing Model; Schumpeterismus; Innovationswettbewerb; Unternehmenswert; Patent; Schätzung; USA